Chyme Reinfusion Reducing the Postoperative Complications After Definitive Surgery for Small Intestinal Enteroatmospheric Fistula: A Cohort Study - Tian, Weiliang; Zhao, Risheng; Xu, Xin; Zhao, Yunzhao; Luo, Shikun; Tao, Shen; Yao, Zheng (Frontiers in Nutrition, 2022)
Abstract Purpose: This study is aimed to reveal the role of preoperative chyme reinfusion(CR) in reducing the complications occurring after definitive surgery(DS) for small intestinal enteroatmospheric fistula(EAF). Methods: From January 2012 to December 2019, the patients with small intestinal EAF and receiving a definitive surgery were recruited. Depending on whether the CR has been performed, these patients were divided into either the CR group or the non-CR group. Then, Propensity Scores Match(PSM) was used to further divide these patients into the PSM CR group or the PSM none-CR group. The clinical characteristics exhibited by the groups were analyzed, and the effect of preoperative CR was investigated. Result: There were a total of 159 patients were finally recruited with 72 patients in the CR group and 87 patients in the non-CR group. The postoperative complications were manifested in a total of 126 cases (79.3%). There were 49 cases in the CR group, and 77 cases in the non-CR group. CR was associated with the occurrence of postoperative complications ( multivariate OR=0.289; 95% CI: 0.123-0.733; P=0.006 ). After 1:1 PSM, there were 92 patients included. The postoperative complications were observed in 67 out of these 92 patients. There were 26 patients in the PSM CR group, and 41 patients in the PSM non-CR group. CR was associated with postoperative complications ( multivariate OR=0.161; 95% CI: 0.040-0.591; P=0.002). In addition, CR played a role in reducing the recurrence of fistula both before ( multivariate OR=0.382; 95% CI: 0.174-0.839; P=0.017) and after ( multivariate OR=0.223; 95% CI: 0.064-0.983; P=0.034) PSM. There is also a protective factor at play for those patients with postoperative ileus before (multivariate OR=0.209; 95% CI: 0.095-0.437; P<0.001) and after (multivariate OR=0.222; 95% CI: 0.089-0.524; P<0.001) PSM. However, the relationship between CR and incision-related complications was not observed in this study. Conclusion: Preoperative CR is effective in reducing postoperative complications after definitive surgery was performed for EAF.